Why Are Job Seekers Attracted by Corporate Social Performance? Experimental and Field Tests of Three Signal-Based Mechanisms - Jones, David A.; Willness, Chelsea R.; Madey, Sarah (Academy of Management Journal, 2014)
Research on employee recruitment has shown that an organization's corporate social performance (CSP) affects its attractiveness as an employer, but the underlying mechanisms and processes through which this occurs are poorly understood. We propose that job seekers receive signals from CSP that inform three signal-based mechanisms that ultimately affect organizational attractiveness: job seekers' anticipated pride from being affiliated with the organization, their perceived value fit with the organization, and their expectations about how the organization treats its employees. We hypothesized that these signal-based mechanisms mediate the relationships between CSP and organizational attractiveness, focusing on two aspects of CSP: an organization's community involvement and pro-environmental practices. In an experiment (n = 180), we manipulated CSP via a company's web pages. In a field study (n = 171), we measured CSP content in the recruitment materials used by organizations at a job fair and job seekers' perceptions of the organizations' CSP. Results provided support for the signal-based mechanisms, and we discuss the implications for theory, future research, and practice.